Emulsion Polymers of Carboxymethyl Cellulose and Methyl Methacrylate with Sodium Dodecyl Sulfate Surfactant as Soil Stabilizer - Abidin, Akhmad Zainal; Nuriman, R. B. Emil Trisatya; Pradipto, Narendra Afian; Putra, Ridwan P. (Indonesian Journal of Chemical Research, 2022)
Polymer-based materials have gained considerable attention in the road construction sector due to their ability to improve the mechanical strength and durability of soil. In this study, carboxymethyl cellulose-methyl methacrylate (CMC-MMA) emulsion polymers were prepared from different MMA to CMC mass ratios with sodium dodecyl sulfate surfactant. The synthesized materials were homogeneously mixed with laterite soil, and their unconfined compressive strengths were measured using dry and wet methods on a universal testing machine. The results indicated that the polymers were obtained in high yields with optimum solids content. Characterization using Fourier transform infrared confirmed the homopolymerization probability of monomers in the materials with increased MMA fractions. In addition, the viscosity of the graft-copolymers measured at room temperature was in the range of 1.2-3.2 cP. The polymer-stabilized soils exhibited maximum unconfined compressive strengths of 564 and 162 psi, respectively, obtained from the dry and wet methods. In general, the rise of MMA fraction in the treated soils enhanced the compressive strength of the soil, with a slight increase in soil pH. This study unfolds the potential of cellulose-based materials that can be implemented in soil reinforcement technology.